Resistance to targeted therapies in breast cancer - Prosperi, Jenifer R. (Springer, 2017)
We present an in-depth description of resistance to targeted therapies in breast cancer. Targeted therapies discussed here include those used to treat ER+ or Her2+ breast cancers (i.e., Tamoxifen or trastuzumab) or those targeting signaling pathways aberrantly activated in triple negative breast cancer (i.e., EGFR and Wnt signaling). We have also provided an overview of standard of care as an introduction into the importance of targeted therapy. It is our hope that this volume gives an insight into the landscape of breast cancer treatment, the challenges of targeted therapy, and a glimpse into the future of breast cancer therapy. #xE000.
Keywords: Breast -- Cancer -- Chemotherapy.; Drug resistance in cancer cells.; elektronické knihy; electronic books